Medication understanding and health literacy among patients with multiple chronic conditions: a study conducted in Bangladesh - Fahad Imtiaz Rahman; Farina Aziz; Sumaiya Huque; Sadia Afruz Ether (Journal of Public Health Research, 2020)
Objectives: Medication understanding is critical for patients who suffer from multiple chronic conditions in order to reduce medication error and is often associated with poor health outcomesand low adherence. This study aims to identify the gap of medication knowledge among multiple chronic condition patients in Bangladesh, in order to aid physicians and other healthcare providers in improving health literacy. Methods: Individual interviews of a convenience sample of multiple chronic condition patients in Bangladesh were heldwhere they were asked a number of questions for assessing medication related literacy. Results: More than 26% patients failed to cite the brand name of all their prescribed medications while the rate of patients not knowing the generic names was far worse (88.1%). Nearly 1 out of every 4 patients did not know the purpose of all their medications and more than half of the participants (55%) did not know the strengths of their drugs. While knowledge about medication routes and regimen was satisfactory, awareness regarding risk factors of medicine was lowest of all. Only 1 out of every 4 patients had a habit of reading drug information leaflet. Patient’s ability to correctly state the purpose of their medication seemed to be positively associated with age (p=0.004) and negatively associated with number of medicines taken (p=0.03). Conclusions: Many patients demonstrated poor health literacy regarding medication. Routine review of medications from physician or health provider can significantly improve their health literacy, leading to better treatment outcome and medication adherence.